Agar Diffusion Method for Negative Staining of Microbial Suspensions in Salt Solutions - Anderson, Nan (1972)
Microbial suspensions in a saline medium can be prepared for negative staining by a simple agar diffusion method that achieves a high degree of particle concentration.